Clinical profile and etiology of children presenting with prolonged fever in tertiary care centre of Southern Rajasthan - Sanadhya, Anuradha; Setia, Sakshi; Goyal, Suresh; Kachhwaha, Ritika (International Journal of Contemporary Pediatrics, 2023)
Background: Fever is the most common complain of a child presenting to a health care setting. A prolonged fever however, is an intriguing challenge for clinicians and remains overly medicated and inappropriately worked up, provided a systemic approach is not followed. Our study aims to find the etiologic diagnosis in these cases of prolonged fever. Methods: The present study was conducted in a tertiary care hospital in southern Rajasthan over a period of 12 months from November 2021 to October 2022. Our descriptive, observational study enrolled 150 children who were prospectively followed during their stay in hospital. Each patient was subjected to a set of mandatory investigations followed by other investigations as per the diagnostic clues. Patients were monitored closely during their course of stay until discharge, at which the final diagnosis was charted. Results: A diagnosis could be reached for 138 patients (92%) and in 12 patients (8%), the cause of fever remained undiagnosed until discharge/death. Out of the 138 patients diagnosed, 118 patients (85.5%, 78.6% overall) had an infection as the cause of fever and 20 cases (14.49%,13.3% overall) had a non-infective etiology. Conclusions: Infections are the most common cause of prolonged fever in pediatric population - tuberculosis being the most frequent infection. Hematological malignancies were found as an emerging cause of prolonged fever in our study.